PENGARUH NILAI PENERBITAN, RATING PENERBITAN, UMUR OBLIGASI SYARIAH TERHADAP REAKSI PASAR MODAL - Wijayaningtyas, Putri; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the influence of issuance value, issuance rating, and the age of Islamic bonds(sukuk) to the reaction of capital market which is measured by using cumulative abnormal return. Thepopulation is all companies who have issued their Islamic bonds and have been listed in Indonesia StockExchange in 2003-2014 periods. The sample collection technique has been done by using purposive samplingmethod and based on the determined criteria, 43 Islamic bonds of 18 Islamic bonds issuance companies whichhave met the criteria. The analysis technique has been done by using multiple linear analyses. Based on theresult of multiple linear regressions analysis, the significance level is 5%. The result of this research shows thatthe Islamic bonds (sukuk) issuance value variable has significant and negative influence to the reaction of capitalmarket, the Islamic bonds (sukuk) issuance rating does not have any significant and negative direction influenceto the reaction of capital market, and the age of Islamic bonds (sukuk) variable does not have any significantinfluence to the reaction of capital market with negative direction.Keywords: Sukuk Issuance value, Sukuk Issuance Rating, Sukuk Age, Reaction of Capital Market